Family Support for Coronary Heart Disease (CHD) Patients in Utilizing Health Information and Services - Asrina, Andi; Marwono, Marwono; Yusriani, Yusriani; Prihatin Idris, Fairus (Window of Health : Jurnal Kesehatan, 2023)
The morbidity and mortality rate of Coronary Heart Disease (CHD) in Indonesia is increasing every year. The results of the 2019 Basic Health Research showed that 1.5% or 15 out of 1000 Indonesians suffer from CHD. The lack of health literacy of CHD patients and their families related to symptoms, risks, lifestyle, and treatment of CHD will further worsen the patient's condition. The purpose of this study was to analyze family support in coronary heart disease (CHD) patients in the use of information and health services. Qualitative research methods with a phenomenological approach and data collection techniques are used through in-depth interviews, observations, and documentation. There were eight research informants consisting of one doctor as a key informant, two supporting informants, and five ordinary informants with criteria for a patient's condition that was stable, communicative, and willing to be an informant. The results showed that the ability of patients to receive and manage information, called health literacy in CHD patients and their families, is still low because they lack the ability to receive and manage information from doctors and lack independent information search efforts. The conclusion of this study is that access to information, receipt, and management of information are very important to improve the health literacy of CHD and their families.